2023
DOI: 10.1111/jcpp.13786
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Integrated healthcare for children and young people in secondary/tertiary care – a systematic review

Abstract: Background: Children and young people (CYP) with comorbid physical and/or mental health conditions often struggle to receive a timely diagnosis, access specialist mental health care, and more likely to report unmet healthcare needs. Integrated healthcare is an increasingly explored model to support timely access, quality of care and better outcomes for CYP with comorbid conditions. Yet, studies evaluating the effectiveness of integrated care for paediatric populations are scarce. Aim and Methods: This systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
(263 reference statements)
0
2
0
Order By: Relevance
“…reduced stigma and barriers, feasibility across most healthcare contexts, etc.). Previous reviews have reported positive data on primary [111,112], secondary and tertiary integration interventions [113] in terms of better accessibility to health services, reduction of waiting times and better early detection of health problems and treatment. Furthermore, health services should have a more widespread presence throughout the territory, particularly primary care, even in the most rural areas, with the possibility of carrying out home interventions.…”
Section: Juniper Online Journal Of Case Studiesmentioning
confidence: 99%
“…reduced stigma and barriers, feasibility across most healthcare contexts, etc.). Previous reviews have reported positive data on primary [111,112], secondary and tertiary integration interventions [113] in terms of better accessibility to health services, reduction of waiting times and better early detection of health problems and treatment. Furthermore, health services should have a more widespread presence throughout the territory, particularly primary care, even in the most rural areas, with the possibility of carrying out home interventions.…”
Section: Juniper Online Journal Of Case Studiesmentioning
confidence: 99%
“…As a result of advancements in modern medicine, conditions that were once lethal have transformed into chronic illnesses. This transformation has led to increased survival rates and aging of the population, with higher prevalence and severity of chronic and comorbid conditions, also among paediatric patients [ 3 , 4 ]. A growing number of children and adolescents with chronic conditions face the risk of cognitive, social, and emotional setbacks.…”
Section: Introductionmentioning
confidence: 99%